Complicações cardiovasculares em pacientes com megaesôfago chagásico submetidos à cirurgia de Serra Dória - Campos Junior, Eumildo de (2011)
Dysphagia caused by chagasic megaesophagus compromises the clinical status and quality of life of patients. In this context, the Serra Dória s operation is a useful procedure in cases of advanced or recurrent disease. Little is known about the cardiovascular complications related to this surgery. Objective: This study aim to identify preoperative risk factors associated with cardiovascular complications after Serra Dória s operation in patients with megaesophagus caused by Chagas disease at the hospital period to document the data in order to better preoperative evaluating of these of these patients. Methods: This is a retrospective study evaluating patients who underwent the Serra Dória s operation at the General Surgery Service of Hospital de Base (FUNFARME), Faculty of Medicine of Sao Jose do Rio Preto (FAMERP) from 1998 to 2010. Initially, we assessed 103 medical records and excluded from the study 16 patients with idiopathic achalasia and 11 incomplete charts; therefore, the study population consisted of 76 patients with chagasic megaesophagus who underwent Serra Dória s procedure. The study was approved by the Ethics in Research Committee No. 254/2011. The following preoperative variables were included in the multivariate stepwise regression analysis: the model: age, sex, degrees of megaesophagus, operation for recurrence of symptoms, need for transfusion of red blood cells, blood pressure, electrolytes, comorbidities, electrocardiographic findings and degree of surgical risk. Cardiovascular complications were as follows: levels of hypotension and hypertension and cardiac arrhythmias without hemodynamic instability observed during the surgery and in the postoperative period. Student s t test was used in the comparison of continuous variables, whereas the chi-squared test was used in the comparison of categorical variables. Variables associated with the presence of cardiovascular complications at the p<0.05 were included in multivariate logistic stepwise regression. Those that remained associated with the presence of cardiovascular complications were considered independent variables to predict the appearance of cardiovascular complications. Results: The mean age was 61 ±10 years with male predominance (42, 55%). Most patients were classified as advanced megaesophagus (65, 86%); 36(47%) of them had relapsed megaesophagus. In 22(29%) of cases there was at least one comorbidity, with hypertension being the most frequently found (25, 30%). In 34(45%) patients the surgical risk was classified as moderate to severe. Among the electrocardiographic findings found preoperatively, sinus rhythm was found in 68(89%) patients, and right bundle-branch block in 28(37%). Cardiovascular complication was observed in 29(38%) patients, with prevalence of hypotension in various levels (14, 41%), followed by cardiac arrhythmias in 12(35%). The largest number of cardiovascular complications occurred during the immediate postoperative period. Variables associated with the presence of complications in the univariate model were age (p=0.003) and left bundle-branch block (p= 0.02). However, only the aged above 61 years of age was an independent predictor of cardiovascular complications in the postoperative Serra Dória s operation. Conclusion: Age is an independent predictor of cardiovascular complications following the Serra Dória s procedure.